THE EFFECT OF SOCIAL CAPITAL ON LOAN REPAYMENT BEHAVIOR OF THE POOR (A Study on Group Lending Model (GLM) Application In Islamic Microfinance Institution) - Sanrego, Yulizar D.; Antonio, M. Syafi’i (Journal of Indonesian Economy and Business, 2013)
Market failures in the financial system may be indicated by the absence of opportunitiesfor the poor to get financial services. This also happens in the practice of Islamicbanking. For this reason it is popping up a lot of non-market institutions - Islamic MicrofinanceInstitutions (IMFi) is one of them - which tried to cover up the weaknesses ofbanking practices. However, the development IMfi is not effective in alleviating povertyand not much different behavior from most banks. In turn, appear Islamic Microfinancebasedgroups in the hope of further empowering the poor and ensure that financialservices can be viable and able to repay their loans with three main approaches thatimplemented simultaneously; (1) spiritual approach (2) financial approach and (3) socialapproach. This study wanted to prove empirically that Islamic Microfinance -based groupscan ensure that the poor deserve to get financial services and are able to repay their loanon time. Using Structural Equation Model the study proved that Social Capital valueswhich embedded within the Islamic Microfinance-based groups influence the behavior ofthe poor in repaying their debts. As a policy recommendation, Islamic Bank shouldconsider to prefer Islamic Microfinance-based groups as partners in the realization oftheir linkage program for the poor so that poverty alleviation program can be optimallyimplemented.Keywords: Social Capital, Group Lending Model (GLM), Repayment Behavior